GATA3 germline variant is associated with CRLF2 expression and predicts outcome in pediatric B‐cell precursor acute lymphoblastic leukemia. Issue 9 (3rd April 2019) - Madzio, Joanna; Pastorczak, Agata; Sedek, Lukasz; Braun, Marcin; Taha, Joanna; Wypyszczak, Kamila; Trelinska, Joanna; Lejman, Monika; Muszynska‐Roslan, Katarzyna; Tomasik, Bartlomiej; Derwich, Katarzyna; Koltan, Andrzej; et al.
Abstract: The germline variant at rs3824662 in GATA3 is a risk locus for Philadelphia‐like acute lymphoblastic leukemia (Ph‐like ALL), the biological subtype of B‐cell precursor (BCP)‐ALL defined by a distinct gene expression profile and the presence of specific somatic aberrations including rearrangements of CRLF2 . In this study, we investigated whether rs3824662 in GATA3 associates with CRLF2 expression in leukemic cells and predicts prognosis in pediatric BCP‐ALL patients treated according to the ALL Intercontinental Berlin‐Frankfurt‐Münster (IC BFM) 2009 (n = 645) and the ALL IC BFM 2002 (n = 216) protocols. High expression of CRLF2 was observed at both protein and mRNA levels (fourfold higher in AA than in CA + CC) among GATA3 AA variant carriers, independent of the presence of P2RY8 ‐ CRLF2 fusion. Additionally, the AA variant at rs3824662 was a significant factor affecting minimal residual disease level at the end of induction phase and overall survival regardless of the risk group and the protocol. The germline variant at rs3824662 in GATA3 is a prognostic factor which associates with CRLF2 expression in leukemic cells supporting the hypothesis that GATA3 may have a regulatory effect on the CRLF2 pathway in pediatric BCP‐ALL.